The relationship between components of negative affect and disordered eating behavior among students: the importance of emotion regulation with religious perspective - Mohamad Reza Khodabakhsh; Fariba Kiani (Shahid Beheshti University of Medical Sciences, 2016)
For downloading the full-text of this article please click here. Background and Objectives: previous research indicates negative affects especially correlate with disordered eating. The aim of this study was to investigate the role of emotion regulation difficulties and negative affects in prediction of disordered eating among student.  Materials and Methods: This cross-sectional study was conducted on 264 students of Allameh Tabataba'i University who were selected by multiple cluster sampling. Participants responded to the questionnaires. Data were analyzed with SPSS V.20 using stepwise Regression and Correlation with α=0.01. Results: Results showed that there was significant internal correlation among emotion regulation difficulties, negative affects and disordered eating behaviors (p<0.01). Also, stepwise regression analysis indicated that emotion regulation difficulties and negative affects significantly predicted, respectively, 57% and 43% of the variance of disordered eating behaviors (p<0.01). Conclusion: This study results suggest the importance of negative affects and emotion regulation difficulties in prediction of disordered eating behaviors. Attention to religious resources existed on the importance of emotion regulation; will be able to assist to individuals in promoting their own health based on religious teachings. Keywords:  Emotion Regulation, Negative Affects, Disordered Eating Behavior, Student. For downloading the full-text of this article please click here.